2020
DOI: 10.1016/j.xphs.2019.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Design of Antibody-Based Therapeutics

Abstract: Keywords: antibody(s) antibody drug(s) antibody drug conjugate(s) (ADC) physicochemical properties pharmacokinetics monoclonal antibody(s) immunotherapy IgG antibody(s) drug design developability a b s t r a c t Antibody-based proteins have become an important class of biologic therapeutics, due in large part to the stability, specificity, and adaptability of the antibody framework. Indeed, antibodies not only have the inherent ability to bind both antigens and endogenous immune receptors but also have proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
154
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 330 publications
(557 reference statements)
1
154
0
2
Order By: Relevance
“…The advent of antibody-based immune therapies has revolutionized the treatment of several human disease states. 34,35 Over the past decade, a primary application of these immunotherapies has been the treatment of malignancies by targeting immune checkpoint molecules. 36 While antibody-based therapeutics are enjoying an unprecedented level of success in the clinic by targeting cells of the immune system, a number of clinical trials have reported adverse reactions, including CRS.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of antibody-based immune therapies has revolutionized the treatment of several human disease states. 34,35 Over the past decade, a primary application of these immunotherapies has been the treatment of malignancies by targeting immune checkpoint molecules. 36 While antibody-based therapeutics are enjoying an unprecedented level of success in the clinic by targeting cells of the immune system, a number of clinical trials have reported adverse reactions, including CRS.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of self-interaction, the diffusion interaction parameter (kD) was determined by DLS. Highconcentration samples were diluted with the buffers of interest (20 mM sodium acetate pH 5.5 and 10 mM histidine hydrogen chloride pH 6.5) to obtain a concentration of 20 mg/mL, filtered through 0.22 µm filters, and diluted in filtered buffers (with desired pH and ionic strength) to obtain lower concentration samples (2,5,10,15, and 20 mg/mL), which were then added to the microplate. The kD was determined by a linear fit of the measured (mutual) diffusion coefficients as a function of concentration.…”
Section: Assessment Of Aggregation and Self-interaction By Dynamic LImentioning
confidence: 99%
“…It is anticipated that mAbs will remain an important part of human health improvement for years to come. 2 Approximately nine out of every 10 drug candidates fail to win approval, i.e.,, 90% of drug candidates will fail during clinical development; possibly over 99% if preclinical stages of development are also included. 3 This failure rate has huge implications for the overall cost of drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies are an important class of biologics-based therapeutics with clear advantages of specificity and efficacy. 1,2,3 The high cost and long development times, however, present key challenges in the accessibility of monoclonal antibody therapeutics. 4,5 To quickly respond to known and new pathogens and disease, and to provide affordable, high quality treatment to patients around the globe, a molecule must be designed for activity; but it must also be made developable and safe for patients.…”
Section: Introductionmentioning
confidence: 99%